The Prognosis of Single Hormone Receptor-Positive Breast Cancer Stratified by HER2 Status - Zhao, Hengqiang; Gong, Yiping (Frontiers in Oncology, 2021)
Single estrogen receptor (ER)+ and progesterone receptor (PR)+ tumors account for about10% of all breast cancers. However, the prognosis of these single hormone receptor-positive (HR+) tumor remains unclear. We aimed to investigate the characteristics of single HR+ breast tumors according to HER2 status in order to improve the treatment of patients with single HR+. Patients from the SEER program (2010-2016) were divided into ER+PR-, ER-PR+, ER+PR+ and ER-PR- molecular subtypes stratified by HER2 status. Overall survival (OS) was compared by Kaplan–Meier curves after propensity score matching (PSM). A total of 203,406 patients were enrolled. Single ER+ and PR+ tumors account for 11.9% of the total population. For HER2- subtype, patients with ER+PR- (n = 16906 pairs) and ER-PR+ (n = 1395 pairs) had worse OS than those with ER+PR+ with hazard ratio (HR) and 95% confidence interval (CI) of 1.52 (1.41-1.64) and 2.25 (1.76-2.88), respectively; ER+PR- showed better OS than ER-PR+ (n = 1394 pairs) and ER-PR- (n = 9626 pairs) with HR (95% CI) of 1.32 (1.06-1.65) and 1.44 (1.33-1.55), respectively; ER-PR+ had similar OS relative to ER-PR- (n = 1395 pairs) after PSM. For HER2+ subtype, patients with ER-PR+, ER+PR-, and ER-PR- had similar OS; ER+PR+ showed similar prognosis compare with ER-PR+ (n = 535 pairs), but had better OS than ER+PR- (n = 5376 pairs) and ER-PR- (n = 8143 pairs) after PSM. In addition, ER+PR+HER2+ showed similar OS compared with ER+PR+HER2- after PSM. In conclusion, single PR+ tumors were less likely to benefit from endocrine therapy than single ER+ tumors, and may be treated as ER-PR- tumors in HER2- subtype. In HER2+ patients, both single ER+ and PR+ tumors failed to benefit from endocrine therapy, and should be treated as HER2+ tumors.